Implementasi Pendekatan Multidimensional Guru Aqidah Akhlak dalam Penanaman Sikap Percaya Diri - Hakim, Arif Rahman; Wijono, Hani Adi; Sugiyanto, Sugiyanto; Setyawan, Ari; Khulailiyah, Ahsanatul (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2025)
This study analyzes the role of Aqidah Akhlak teachers in cultivating students' self-confidence at MTsN 9 Jombang. Through the descriptive qualitative method, this research reveals the multidimensional strategies applied by teachers in developing students' self-confidence. Data collection was carried out through interviews with the head of the madrasa, the deputy head of student affairs, Aqidah Akhlak teachers, and students, and supported by observation and documentation. The results showed that the Aqidah Akhlak teacher acts as a guide who provides information, motivation, and direction to students. The cultivation of self-confidence is done through various methods, including giving advice, habituation, rewards, and personal approaches. Madrasahs also facilitate the development of students' self-confidence through extracurricular activities and comprehensive evaluations involving daily tests, individual and group assignments, and question-and-answer methods. Collaboration between the madrasah head, the head of student affairs, the Aqidah Akhlak teacher, and the counseling teacher creates an educational ecosystem that supports the development of students' self-confidence. This research contributes to the development of a holistic guidance model that integrates pedagogical, psychological, and spiritual aspects in Islamic education, offering a new perspective on the approach to character education in the madrasah environment